Simplified Event-Based Load Shedding Scheme for Frequency Stability in an Isolated Power System With High Renewable Penetration. El Hierro: A Case Study - Sarasúa, José Ignacio; Pérez-Díaz, Juan Ignacio; Martínez-Lucas, Guillermo; Fernández-Muñoz, Daniel (Frontiers in Energy Research, 2021)
This study presents a novel approach to calculate the load to be shed in El Hierro isolated power system in generation tripping events. The proposed shedding law is based on a linear regression model. The regression model is obtained by means of offline dynamic simulations in a set of representative test cases. The proposed shedding law has been compared to the under-frequency load shedding scheme currently utilized in El Hierro, considering three different implementation schemes. The results of this study demonstrate that the proposed shedding law can contribute to reduce the average amount of load shed in generation tripping events and meet the requirements of the system’s frequency with a moderate investment in smart power management devices.